2009
DOI: 10.1177/0960327109107044
|View full text |Cite
|
Sign up to set email alerts
|

Use of pralidoxime without atropine in rivastigmine (carbamate) toxicity

Abstract: Some experimental models suggest that the use of pralidoxime in carbamate toxicity is deleterious. Although pretreatment with atropine minimizes the adverse effect of pralidoxime reported in these models, concerns over the risks of pralidoxime in humans with carbamate poisoning continue. We present a unique case of carbamate toxicity treated successfully with pralidoxime alone. An 80-year-old woman with Alzheimer’s dementia presented to the emergency department with 3-4 days of lightheadedness, vomiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…14 Adult case reports report significant morbidity and death from rivastigmine exposure. [15][16][17] Our findings of higher rates of reported symptoms and health care facility evaluations with rivastigmine exposures are consistent with the increased morbidity seen in these prior case reports, and merit attention to more exposures from this drug in the years ahead.…”
Section: Discussionsupporting
confidence: 85%
“…14 Adult case reports report significant morbidity and death from rivastigmine exposure. [15][16][17] Our findings of higher rates of reported symptoms and health care facility evaluations with rivastigmine exposures are consistent with the increased morbidity seen in these prior case reports, and merit attention to more exposures from this drug in the years ahead.…”
Section: Discussionsupporting
confidence: 85%
“…However, due to the fact that the temporary AChE-carbamate bond is rapidly reversed, this test must preferably be performed immediately, seeing that the diagnostic test results could become inconclusive if the test is not performed within a few hours 27 . A blood sample may be collected prior to initiating the treatment and the AChE concentration determined as soon as possible.…”
Section: Diagnosismentioning
confidence: 99%
“…In contrast to organophosphate toxicity, the carbamate-induced inhibition of AChE is rapidly reversible with hydrolysis of the carbamylated complex often occurring within an hour 31 . The use of oximes in carbamate poisoning is controversial 5,12,29,55 or even contraindicated 27,50 and is therefore not recommended for the treatment of aldicarb poisoning in dogs. Many studies have indicated that the treatment of carbamate poisonings in animals with oximes has resulted in a protective ratio of less than 1 (i.e.…”
Section: Oximesmentioning
confidence: 99%
See 1 more Smart Citation
“…The American Food and Drug Administration (FDA) states that opioids poses the highest risk of harm and death, among approved transdermal patches, because of their risk to cause respiratory depression [7] and has, along with other organizations, issued warnings regarding unsafe use of these patches [8,9]. There are also previous reports of serious and fatal cases due to erroneous administration of multiple patches of rivastigmine, an anticholinergic drug used to treat dementia [4,10]. Prevalence and characteristics of medications errors related to transdermal opioid patches has not been systematically compiled and presented in the scientific literature and such information is needed to develop effective preventive measures.…”
Section: Introductionmentioning
confidence: 99%